EUROPEAN POLICY CONCERNING THE PROTECTION OF THE QUALITY OF THE ENVIRONMENTAL FACTOR - WATER - FLORICA BRASOVEANU; ALEXANDRU PETRU LISIEVICI BREZEANU (Challenges of the Knowledge Society, 2012)
European Union environmental policy, as was established in the EC Treaty aims at ensuring environmental sustainability activities through its inclusion in EU sectoral policies, by developing measures to prevent by following the basic principles of sustainable development and by taking joint responsibilities. Environmental legislation is one of those tools that combine management of natural resources with the prevention and control of the pollution. These laws attempt to prevent, or at least limit the effects of environmental degradation caused by the phenomenon of pollution. Environmental legislation should primarily be flexible in the sense to allow the fulfillment of current and the future goals in order to stimulate sustainable development concept and to base on general criteria for the purposes of allowing the extension to complex environmental problems. The environmental legislation is due to focus on integrating the source - effect policy, that is to focus on regulations for issuing permits for pollution, but also the responsibility of companies and citizens.Despite the significant improvements that have occurred especially in reducing air and water pollution, European legislation should be developed further. It is true that there are still many points that require completion and perfection, but the path followed is the best. In the European Union the process of implementation and adoption of new regulations on environmental protection (regulations, directives, decisions,recommendations) to combat the causes of degradation of environmental quality and life quality time with them continues.